Answer:
Step-by-step explani belive you add it if it is improper then simplify hope it helps
Answer:
+2
Step-by-step explanation:
=> ![(2-3x)(x^2-5)](https://tex.z-dn.net/?f=%282-3x%29%28x%5E2-5%29)
=> ![(2x^2-10-3x^3+15x)](https://tex.z-dn.net/?f=%282x%5E2-10-3x%5E3%2B15x%29)
<em>Arranging it in descending order</em>
=> ![-3x^2+2x^2+15x-10](https://tex.z-dn.net/?f=-3x%5E2%2B2x%5E2%2B15x-10)
<u><em>So, the coefficient of x² in this expression is +2</em></u>
Answer: x<4
Given the inequality:
![10x>2(8x-3)-18](https://tex.z-dn.net/?f=10x%3E2%288x-3%29-18)
We want to solve the inequality for x.
First, distribute the bracket on the right side of the inequality.
![\begin{gathered} 10x>2(8x)-2(3)-18 \\ 10x>16x-6-18 \\ 10x>16x-24 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%2010x%3E2%288x%29-2%283%29-18%20%5C%5C%2010x%3E16x-6-18%20%5C%5C%2010x%3E16x-24%20%5Cend%7Bgathered%7D)
Next, subtract 10x from both sides of the inequality.
![\begin{gathered} 10x-10x>16x-10x-24 \\ 0>6x-24 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%2010x-10x%3E16x-10x-24%20%5C%5C%200%3E6x-24%20%5Cend%7Bgathered%7D)
Add 24 to both sides of the inequality.
![\begin{gathered} 0+24>6x-24+24 \\ 24>6x \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%200%2B24%3E6x-24%2B24%20%5C%5C%2024%3E6x%20%5Cend%7Bgathered%7D)
Divide both sides of the inequality by 6.
![\begin{gathered} \frac{24}{6}>\frac{6x}{6} \\ 4>x \\ \implies x](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B24%7D%7B6%7D%3E%5Cfrac%7B6x%7D%7B6%7D%20%5C%5C%204%3Ex%20%5C%5C%20%5Cimplies%20x%3C4%20%5Cend%7Bgathered%7D)
The solution to the inequality is x<4.
A. 3/2
b.0.5
c.you have to add them